2021
DOI: 10.1126/sciadv.abd6034
|View full text |Cite
|
Sign up to set email alerts
|

Natural climate solutions for Canada

Abstract: Alongside the steep reductions needed in fossil fuel emissions, natural climate solutions (NCS) represent readily deployable options that can contribute to Canada’s goals for emission reductions. We estimate the mitigation potential of 24 NCS related to the protection, management, and restoration of natural systems that can also deliver numerous co-benefits, such as enhanced soil productivity, clean air and water, and biodiversity conservation. NCS can provide up to 78.2 (41.0 to 115.1) Tg CO2e/year (95% CI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 64 publications
1
88
1
Order By: Relevance
“…These considerations have merit in a context where stress factors compound each other, affecting the health of trees and forests ( 62 ). Our empirical assessment of tree growth response to cold-season freeze in boreal forests can support efforts to represent tree growth processes in global vegetation models, which is urgently needed for improved nature-based solutions to mitigate, and adapt to, climate change ( 4 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…These considerations have merit in a context where stress factors compound each other, affecting the health of trees and forests ( 62 ). Our empirical assessment of tree growth response to cold-season freeze in boreal forests can support efforts to represent tree growth processes in global vegetation models, which is urgently needed for improved nature-based solutions to mitigate, and adapt to, climate change ( 4 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of 4R nitrogen (N) practices to mitigate nitrous oxide emissions has been recognized by the Field to Market sustainability organization (Field to Market, 2017) and by the province of Alberta (Alberta Government, 2014). An assessment of natural climate solutions for Canada concluded that increased adoption of 4R practices could reduce greenhouse gas emissions in Canada by an additional 6.9 million short tons of carbon dioxide equivalents annually by 2030, contributing 3% of Canada's commitment to the Paris Accord (Drever et al, 2021).…”
Section: Nitrous Oxide Emissionmentioning
confidence: 99%
“…To date, these estimates remain vague and do not provide a clear characterization of the state of agricultural situation on the dykelands. This is especially pertinent in the context of current and future climate change [10][11][12]. This situation was outlined in a study by van Proosdij and Page [13], which predicted a relative sea-level rise in Nova Scotia, ranging from 70 to 140 cm over the next century and will therefore increase the vulnerability of the dyke system to storm surges [13].…”
Section: Of 14mentioning
confidence: 99%
“…Knowing when and how to manage these scenarios is especially pertinent, considering that most of these dyke infrastructures will have to be maintained in the coming years due to rising sea levels. Unfortunately, very little information on what is being grown and how many hectares of crops are being grown are currently available for dykelands [10][11][12]. Given the predictions of rising sea levels, challenges regarding a proper assessment of the resources of the dykelands must be addressed.…”
Section: Of 14mentioning
confidence: 99%